2010
DOI: 10.1186/1750-1326-5-19
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic pathways mediating oligomeric Aβ42 neurotoxicity

Abstract: BackgroundOne pathological hallmark of Alzheimer's disease (AD) is amyloid plaques, composed primarily of amyloid-β peptide (Aβ). Over-production or diminished clearance of the 42 amino acid form of Aβ (Aβ42) in the brain leads to accumulation of soluble Aβ and plaque formation. Soluble oligomeric Aβ (oAβ) has recently emerged to be as a likely proximal cause of AD.ResultsHere we demonstrate that endocytosis is critical in mediating oAβ42-induced neurotoxicity and intraneuronal accumulation of Aβ. Inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 91 publications
(73 reference statements)
2
63
1
Order By: Relevance
“…A recent study showed that, in mice with a toxin-induced compromise of the blood-brain barrier, fluorescently labeled A␤ that is injected into the tail vein can accumulate intracellularly in pyramidal neurons in the cerebral cortex [110]. The results presented by the authors provide direct evidence that neurons can take up extracellular A␤, one of mechanisms that has been proposed is the endocytocis of A␤ oligomers [111].…”
Section: Intracellular A␤ Oligomer Toxicitymentioning
confidence: 89%
“…A recent study showed that, in mice with a toxin-induced compromise of the blood-brain barrier, fluorescently labeled A␤ that is injected into the tail vein can accumulate intracellularly in pyramidal neurons in the cerebral cortex [110]. The results presented by the authors provide direct evidence that neurons can take up extracellular A␤, one of mechanisms that has been proposed is the endocytocis of A␤ oligomers [111].…”
Section: Intracellular A␤ Oligomer Toxicitymentioning
confidence: 89%
“…For example, inactivated RhoA can reduce the uptake of oligomeric Aβ42 in N2A cells as part of the mechanism to defend cells from oligomeric Aβ42-induced neurotoxicity [73]. Activated RhoA inhibits transferrin-receptor-mediated endocytosis in Hela cells [57], the muscarinic acetylcholine receptors trafficking to the plasma membrane in HEK293 cells [74] and the uptake of fetuin-A in bovine vascular smooth muscle cells [75].…”
Section: Role Of Rho Gtpases In Vesicular Transportmentioning
confidence: 99%
“…The clathrin coat then depolymerizes followed by delivery of the cargo to early endosomes and then to late endosomes/lysosomes for degradation or to recycling endosomes for recycling of the receptor back to the PM [45]. Although the evidence for human amylin internalization pathways, particularly in pancreatic cells is scarce [4], [49], [50], many studies have revealed the involvement of a multitude of endocytotic pathways in uptake of other amyloid peptides in a variety of cell types and tissues [47], [51][54]. For example, low density lipoprotein 1 receptor has been shown to internalize soluble forms of β-amyloid complexed with apolipoprotein E mainly through the CME in neuroblastoma and neuronal cell lines [52].…”
Section: Introductionmentioning
confidence: 99%